Bioalcohol production from acidogenic products via a two-step process: A case study of butyric acid to butanol. (15th October 2019) - Cho, Seong-Heon; Kim, Juyeon; Han, Jeehoon; Lee, Daewon; Kim, Hyung Ju; Kim, Yong Tae; Cheng, Xun; Xu, Ye; Lee, Jechan; Kwon, Eilhann E.
Graphical abstract: Highlights: A full study of butanol production using experiments and simulations was conducted. A two-step process to produce butanol from butyric acid is suggested. Butanol can be produced with a 0.231 g/g yield via the two-step process. Minimum selling price of butanol is US$ 3.388 per gallon of gasoline equivalent. Abstract: This article presents the full study (lab-scale experimental study and large-scale techno-economic analysis) results of a two-step catalytic process for the conversion of organic waste–derived butyric acid to butanol. The two-step process consists of the (1) esterification of butyric acid to methyl butyrate and (2) hydrogenolysis of this methyl butyrate to butanol. The first reaction, esterification of butyric acid, was optimized using carbon-based catalysts. The production of butanol from methyl butyrate via hydrogenolysis was investigated using bimetallic Pt–Co catalysts. The hydrogenolysis of methyl butyrate on these catalysts under optimal conditions of 250 °C, 5 MPa H2, and a feed/catalyst weight ratio of 11.2 led to 54.1% selectivity toward 1-butanol. Based on the experimental results, an integrated process simulation model was developed to determine the economic potential of the two-step production of butanol from butyric acid. Using this model, the techno-economic feasibility of the two-step process was analyzed. The minimum selling price (MSP) of 1-butanol produced from butyric acid using this process was US$ 3.388 per gallon of gasoline equivalent (GGE). This MSP is in the range of recent biofuel market prices of US$ 2.03/GGE to US$ 3.83/GGE.